Representation of the Pancasila Learner Profile in Grade 12 EFL textbooks with Merdeka Curriculum - Alvandha Adindra; Misbahul Amri; Lestari Setyowati (Green Publisher Indonesia, 2025)
This study investigates the extent to which visuals and visual texts in the Merdeka curriculum EFL textbooks for grade XII depict the characteristics of a good Pancasila student. The research employs a qualitative approach and content analysis to examine the official textbook